Effects of Tempeh Flour Snack Bar on Organoleptic Tests and Nutritional Content as a Snack for Athletes - Sari, Nadia Puspita (Sport and Nutrition Journal, 2024)
Introduction: Athletes need snacks, one of which is a snack bar. Tempe flour snack bar and watermelon rind can help restore muscle damage after sports activities. This study aims to determine the effect of tempeh flour snack bars with the addition of watermelon rind on organoleptic tests and nutritional content referring to SNI 0-4216-1996 quality standards and determine the best formula. Methods: This type of research is an experimental study using a Completely Randomized Single Factor Design. There are three formulas with different kinds of watermelon rind: SBT 1 of 6 g, SBT 2 of 4 g, and SBT 3 of 8 g. Analysis of nutritional content using the calculation method, Wilbull, titimetry. Data analysis used Kruskall Wallis, One Way ANOVA, and Duncan's test using SPSS software. Results: The results showed no significant difference in the organoleptic test of the three formulas. There is a substantial difference in nutritional content. The best formula is SBT 1, which has 385.49 kcal/g energy and 14.94 g protein. Tempe flour snack bar products are said to contain high energy because they exceed the quality standards of SNI 0-4216-1996.